2015
DOI: 10.1159/000369560
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obstructive Sleep Apnea Syndrome and Apolipoprotein E Genetic Variants

Abstract: Background: Clinical and epidemiological studies indicate that obstructive sleep apnea syndrome (OSAS) has a strong genetic basis. Objectives: To investigate the apolipoprotein E (APOE) alleles as a genetic risk factor in OSAS. Methods: A total of 73 patients (37 male) were included. All underwent full-night polysomnography and were evaluated for APOE alleles. Results: The mean age was 51 ± 12 years. Forty-two of the patients had OSAS. The APOE3 allele was found in 97.3% (71/73) of the study population. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…According to a study, which compared individuals with different degrees of SDB, there was no association between SDB and APOE -ε4 (18) . More existing studies found no association between APOE -ε4 and OSAS (16, 19) .…”
Section: Introductionmentioning
confidence: 88%
“…According to a study, which compared individuals with different degrees of SDB, there was no association between SDB and APOE -ε4 (18) . More existing studies found no association between APOE -ε4 and OSAS (16, 19) .…”
Section: Introductionmentioning
confidence: 88%
“…After exclusions, data were extracted from 14 articles (12 in English and two in Chinese) that fulfilled the predetermined eligibility criteria. 10 23 Figure 1 presents a flow diagram of search strategy and study selection; Table 1 shows the characteristics of all study populations. A total of 19 study populations were available from the 14 included studies, with 3198 patients and 6031 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in many children with OSAS and neurocognitive deficits, there was a high presence of ε4APOE allele, known to be present above all in people suffering from Alzheimer's disease [58]. Through magnetic resonance spectroscopy studies, it has been shown that in children with OSAS, there is a decreased hippocampal volume and focal reductions of gray matter in the frontal and parietal lobes [59,60].…”
Section: The Link Between the Severity Of Respiratory Disturbance In mentioning
confidence: 99%